Underdetermined 2D DOA Estimation for Coherent Signals via Sparse Sensor Array With Nested Moving Sampling Scheme - Jiang, Guojun; Wang, Shaobo; Huang, Jiacheng; Yang, Xuguang; Yang, Yunlong (IEEE signal processing letters, 2025)
In order to improve the performance of target localization based on multi-sensor system, this paper proposes a novel sparse acoustic vector sensor (AVS) array with nested moving sampling scheme, forunderdetermined two-dimensional (2D) direction of arrival (DOA) estimation of coherent target signals. By exploiting the dense sampling of the nested sampling scheme, a synthetic array composed of the original and shifted sparse arrays, is achieved with increased degrees of freedom (DOF) and extended aperture. Based on it, the sparse sampling in the sampling scheme is applied to decorrelate the coherent signals, and then eigenstructure based methods are used for high-accuracy 2D DOA estimation in underdetermined scenario. The simulation results are given to demonstrate the effectiveness of the proposed method over the state-of-the-art techniques.